A case report: Null-cell cardiac lymphoma in an English bulldog - Köster, Liza S.; Newkirk, Kim; Krawec, Philip (Frontiers in Veterinary Science, 2024)
This case report describes a novel example of an extra-nodal null-type lymphoma in the myocardium of a middle-aged English bulldog that presented with signs of right heart failure. An echocardiogram found, in addition to the pericardial effusion, thickened right and left ventricular free walls and interventricular septum. The right ventricular free wall myocardium had multinodular lesions, suspicious for infiltrative disease. The owner elected humane euthanasia and permission for necropsy was obtained. Multifocal left and right ventricular nodules and an incidental aortic root mass were detected, the latter of which later was confirmed as a chemodectoma. Microscopically, the myocardial nodules were sheets of round cells consistent with a high-grade lymphoma. Neoplastic cells were not immunoreactive to CD3 (T-cell) or CD20 and CD79a (B-cell), Mum-1 (plasma cell), CD117 (mast cell) or CD18 (histiocyte). These findings are consistent with a high grade, null-cell type lymphoma.